Akibat Hukum Pembatalan Jual Beli di Aplikasi E-Commerce sebagai Perbuatan Itikad Tidak Baik Berdasarkan KUH Perdata - Fakira, Qania Athaya; Lubis, Syaddan Dintara (Legal Standing : Jurnal Ilmu Hukum, 2025)
The transformation of digital technology and the development of the internet have revolutionized trade activities, one of them is through electronic commerce (e-commerce). This business model offers ease of transactions, time efficiency, and expanded market reach without geographical boundaries. However, this convenience raises legal issues, one of them is unilateral transaction cancellation by the buyer, particularly with the Cash on Delivery (COD) method. From the perspective of Indonesian civil law, unilateral cancellation without a valid reason constitutes a form of default and a violation of the principle of good faith as regulated in Clause 1338 verse (3) of the Civil Code. This study aims to identify legal provisions related to bad faith in unilateral cancellation and to analyze the forms of legal protection for sellers in e-commerce. This study uses a normative juridical research type with a statutory approach. Data collection techniques include literature studies, including primary legal materials such as the Civil Code, Clause No. 8 of 1999 concerning Consumer Protection, and Clause No. 11 of 2008 concerning Electronic Information and Transactions, as well as secondary and tertiary legal materials. The analysis method in this study is qualitative, conducted through an interpretation of the processed legal materials. The results show that unilateral cancellations, particularly in COD systems, cause losses for sellers both financially and non-financially, including damaged goods, repackaging costs, lost potential profits, and psychological stress. Legal protection for sellers includes the right to receive payment as agreed, protection from bad faith consumer actions, and the right to claim compensation under Clause 1243 of the Civil Code. Prevention efforts can be implemented practically, such as reporting to the platform and deactivating the COD option, or legally through lawsuits for breach of contract or unlawful acts. This study presents a novelty approach to the concept of bad faith, which can be considered to be unilateral cancellation.